Knowledge toward Drugs Resistant Tuberculosis in One of the Highest Burden Drug Resistant Country - Ramadhani, Amalia Rizki; Lestari, Bony Wiem; Suryadinata, Hendarsyah (Althea Medical Journal, 2018)
Background: Drug resistant tuberculosis (DR-TB) is the biggest threat in TB case control worldwide. West Java Province is one of the three provinces with the most DR-TB burden in Indonesia. Knowledge level in DR-TB patients influences the perception, health search effort, and patient compliance towards DR-TB treatment. This study was aimed to identify the knowledge level about DR-TB in DR-TB patients at Hasan Sadikin General Hospital. Methods: This cross-sectional, descriptive quantitative study used consecutive sampling. In the study 96 patients were included. Primary data were collected through interview with questionnaire towards DR-TB patients at MDR-TB Clinic Hasan Sadikin General Hospital during September-November 2016. The questionnaire contained sociodemographic data and knowledge about DR-TB which consisted of definition, transmission, risk factors, resistance types, symptoms, medication, and prevention of DR-TB. The collected data were analyzed using statistical software for descripitive statistical analysis.Results: The average age of patients was 38 years (SD±11.7) and mostly ranging from 36–45 years old. Male had a higher distribution compared to female (55.2%). Analysis results showed 20% patients had “Adequate” knowledge level, 34.4% of the patients had “Sufficient” knowledge, and 39.6% of the patients had “Poor” knowledge about DR-TB.Conclusions: DR-TB patients at MDR-TB Clinic Dr. Hasan Sadikin General Hospital Bandung have “poor” knowledge regarding DR-TB.